EPCO-08. CONSERVED FEATURES OF TERT PROMOTER DUPLICATIONS REVEAL AN ACTIVATION MECHANISM THAT MIMICS HOTSPOT MUTATIONS IN CANCER. (14th November 2022) - Suwala, Abigail; Barger, Carter; Soczek, Katarzyna M; Wang, Albert S; Kim, Min Y; Hong, Chibo; Doudna, Jennifer A; Chang, Susan M; Phillips, Joanna J; Solomon, David A; Costello, Joseph F
Abstract: Mutations in the TERT promoter are the single most common non-coding mutation in cancer and represent the genetic underpinnings of tumor cell immortality. Beyond the two most common point mutations, G228A and G250A, which selectively recruit the ETS factor GABP to activate TERT, the significance of other variants in the TERT promoter are unknown. We identified duplications of wildtype sequence within the core promoter region of TERT in 7 different cancer types that have strikingly similar features including size, insertion position, and inclusion of one of the native ETS motifs. Each duplication activates the TERT promoter to a similar level as G228A and G250A and is critically dependent on the insertion site. The GABP tetramer binds to the TERT duplicated promoter sequence by virtue of the native ETS motif and its duplicated version with precise spacing, and it is necessary for the transcriptional activation by all duplications tested. Spatiotemporal analysis in a multifocal glioblastoma shows the duplication is clonal and its activation of TERT is readily detectable at the single cell level and in bulk tumor tissue. We conclude that recurrent TERT promoter duplications of the native ETS sequence are functionally and mechanistically equivalent to the hotspot mutations that confer tumor cell immortality. The shared mechanism of these divergent somatic genetic alterations suggests a strong selective pressure for recruitment of the GABP tetramer to activate TERT .